Pegylated interferon-α-2b reduces corticosteroid requirement in patients with Behçet's disease with upregulation of circulating regulatory T cells and reduction of Th17. Issue 6 (30th September 2014) - Lightman, S; Taylor, S R J; Bunce, C; Longhurst, H; Lynn, W; Moots, R; Stanford, M; Tomkins-Netzer, O; Yang, D; Calder, V L; Haskard, D O
Abstract : Objective: To determine whether the addition of 26 weeks of subcutaneous peginterferon-α-2b could reduce the requirement for systemic corticosteroids and conventional immunosuppressive medication in patients with Behçet's disease (BD). Methods: We conducted a multicentre randomised trial in patients with BD requiring systemic therapy. Patients were randomised to 26 weeks of peginterferon-α-2b in addition to their standard care or to standard care only and followed 6-monthly for 3 years with BD activity scores and quality of life questionnaires. Patients at one centre had blood taken to measure regulatory T cells (Tregs) and Th17 cells. Results: 72 patients were included. At months 10–12, while among the entire patient population there was no difference in the corticosteroid dose or immunosuppression use between the treatment groups (adjusted OR 1.04, 95% CI 0.34 to 3.19), post hoc analysis revealed that in patients who were on corticosteroids at baseline the corticosteroid requirement was significantly lower in the peginterferon-α-2b (6.5 (5–15) mg/day) compared with the non-interferon group (10 (8.25–16.5) mg/day, p=0.039). Furthermore, there was a trend towards an improved quality of life that became significant by 36 months (p=0.008). This was associated with a significant rise in Tregs and a decrease in Th17 cells which was still present at 1 year and 6 months after the interferon was stopped. The safety profile was similar with adverse events in 10% in both groups. Conclusions: The addition of peginterferon-α-2b to the drug regime of BD patients did not significantly reduce their corticosteroid dose required at 1 year. However, in those on corticosteroids at baseline post hoc analysis demonstrated that the addition of peginterferon-α-2b did result in a significant reduction in corticosteroid dose with a significantly improved quality of life and trend to reduce other required immunosuppressive agents. This effect was seen at 1 year and associated with a rise in Tregs suggesting a possible mode for interferon action. Trial registration number: ISRCTN 36354474; EudraCT 2004-004301-18.